Evaluation of Copper Concentration in Subclinical Cases of White Muscle Disease and Its Relationship with Cardiac Troponin I - Ataollahi, Forough (Public Library of Science, 2013)
The present study aims to evaluate the serum level of copper (Cu) in lambs suffering from subclinical forms of white muscle disease (WMD) and its relationship with cardiac troponin I (cTn-I) as a novel biomarker of cardiovascular disorders. Ten milliliters of jugular blood were taken from 200 lambs less than one year old to measure serum concentrations of Cu, selenium (Se), and cTn-I. The subjects were divided into 2 groups, namely, the deficient group which included 36 lambs, and the control group which included 164 lambs according to the reference serum Se concentration (50 ng/mL). Serum Se levels in the deficient group were lower than 50 ng/mL. By contrast, the control group showed Se levels higher than 50 ng/mL. Differences among the serum Cu and cTn-I levels were determined in both groups. The mean ±SD and median of serum Cu and cTn-I levels in the deficient group were lower and higher than those in the control group, respectively. A significant positive correlation was observed between serum Cu and Se levels, and also serum Cu and Se levels showed a negative correlation with serum cTn-I concentrations. Stepwise linear regression analysis showed that serum Cu levels were correlated positively with serum Se levels (p<0.05). Receiver operating characteristic (ROC) curve analysis indicated that the area under curve (AUC) of Cu was significantly higher than that of cTn-I based on the reference diagonal line. It is important to keep in mind that the value of AUC for the ROC curve is between 0.5 and 1.00, in which the lowest accuracy is related to the reference diagonal line with AUC of 0.5. A cut-off was determined to indicate which Cu level can discriminate between affected and healthy lambs. The cut-off level, sensitivity, and specificity of Cu in this study were 144.5 ng/mL, 74%, and 61%, respectively.